Sociology in Algeria between the dominance of the western model and the challenges of local modeling - Amine, Chieb Mohamed; Hala, Krinah (The International tax journal, 2025)
The research paper raises the problem of the dominance of the Western model in sociology in Algeria, and its repercussions on the development of local models that take into account the socio-cultural and historical specificity of Algerian society. It also addresses a number of challenges that stand as an obstacle to the research practice of sociology that would establish an Algerian sociological theory. In conclusion, the research paper proposes strategies for developing Algerian theoretical models capable of explaining its reality, with an emphasis on the need for local researchers to be open to the international academic community.